Increased pH stability via functional group transformation from acidic hydroxyl to basic secondary amine for a series of pyridone based heterocyclic dyes. (May 2017) - Zhao, Xiao-Lei; Chang, Fei-Fan; Feng, Ya-Nan; Qian, Hui-Fen; Huang, Wei
Abstract: Synthetic strategy of functional group transformation has been utilized to modify the acidic hydroxyl (−OH) of a series of pyridone based heterocyclic dyes into basic secondary amine (−NHCH2 CH2 CH2 OCH3 ), so as to improve the color instability of hydrazone dyes under the basic condition. Namely, five pairs of 6-(3-methoxypropylamino)pyridin-2-one based azo dyes have been synthesized showing significantly increased pH stability, which can be verified by corresponding UV–Vis spectra. Successful configuration transformation from the NHN= unit in the hydrazone dyes into the NN− one in the resultant azo dyes is believed to obstruct the proton transfer between the pyridone and azo/hydrazone units (azo-hydrazone tautomerism), thereby enhancing the pH stability especially under the alkaline condition. In addition, different N -substituted groups at the pyridone ring and push-pull electronic substituted groups at the phenyl ring have been selected to make spectral and structural comparisons before and after the functional group transformation. Graphical abstract: Highlights: Functional group transformation is used to modify the hydroxyl of pyridone precursors. Five pairs of 6-(3-methoxypropylamino)pyridin-2-one based azo dyes are synthesized. Azo-hydrazone tautomerism is eliminated by introducing the acid and alkali-stable group. pH Stability of resultant azo dyes is greatly increased compared with the hydrazone dyes.